PUBLIC EXPENDITURE ON HEALTHCARE IN POLAND (2010-2020) - OWCZARCZYK, ANNA (Management and Administration Journal, 2021)
Both expenditure on healthcare and the functioning of the entire healthcare system in Poland stir up considerable controversy and are often discussed in the media. Hospital debts, the low quality of services, and the low availability of specialist medical services form the basis for the discussion of the effectiveness of the healthcare system. Statistical data are also bleak. Total health expenditure in Poland in 2019 amounted to 6.3% of GDP (estimated expenditure), whereas the average for health expenditure in the OECD countries was 8.8%. Therefore, Poland is below the average, and is placed last but four in the ranking (stat.oecd.org). The aim of this article is the presentation of public expenditure on healthcare in Poland from 2010 to 2020. In order to achieve this, the following research methods were used: a critical analysis of the literature, an analysis of statistical data, and - to make the research more transparent and the research results clearer - a tabular method was used. Also, widely accepted measurements were used, such as absolute values in domestic and international currencies, values per capita, and values in relation to the Gross Domestic Product (GDP).oduct (GDP).